Boarding School Management in Developing the Character of Students of the Al-Ihmy Al-Qur'an Tahfidz House Foundation in Medan - Nur Aminah Siregar; Rusydi Ananda; Makmur Syukri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This research is motivated by the problem of moral decadence which is a strategic issue, therefore it needs to be addressed based on precise and accurate data. The purpose of this research is to analyze and describe (1) planning (2) implementation (3) supervision (4) evaluation of boarding school management in developing the character of students at the Al-Ihmy Medan Al-Qur'an Tahfidz House Foundation. This research method uses a qualitative approach. Data sources come from informants (caregivers/ustadz, and students), observations and documents. Data collection techniques use interviews, observations and documentation. Data testing techniques use triangulation techniques. Data analysis techniques use the stages of data reduction, presentation and verification. Research shows that the character education services provided by the Al-Ihmy Medan Al-Qur'an Tahfidz House Foundation are integrated into both classroom and extracurricular activities. All policies are planned by the school and the Islamic boarding school. The integrated character education planning process between the school curriculum and the Islamic boarding school program involves establishing a character development team, consisting of a supervising religious teacher. Scheduling and character-building programs are implemented through collaboration between all members of the boarding school. Implementation is integrated into every student activity. Supervision is aimed at enforcing student disciplinary rules.